Exploring Semantic Component and Expansion: Unpacking the Layers of Meaning in â€œKung Tuyo Na Ang Luha Mo, Aking Bayanâ€ by Amado V. Hernandez - Mar Fernandez Martin; Cristian Gregor E Atacador (Universitas Muria Kudus, 2025)
This study explores the semantic components and expansions of â€œKung Tuyo na ang Luha Mo, Aking Bayan,â€ focusing on the linguistic experiences of the author in the poem, semantic components, semantic expansion, and implications in education. Relational qualitative content analysis was utilized to unpack the poem systematically. The findings highlight significant semantic components and expansion in line/s such as â€œLumuha ka, aking bayan; buong lungkot mo iluhaâ€, Personification, depicted as a person crying, symbolizing national grief under colonial oppression, additionally, â€œKatulad mo ay si Huli, naaliping bayad-utang, katulad mo ay si Sisa, binaliw ng kahirapanâ€, Simile, the nation is compared to Rizalâ€™s tragic characters Juli and Sisa, symbolizing suffering under colonial and systemic oppression. Moreover, with words/phrases like